Climate change and fish culture in Patagonia: present situation and perspectives - Báez, Víctor Humberto (2011)
Temperature increment is one of the most visible aspects of climate change. Reservoirs in Northern Patagonia are the main location for rainbow trout cage aquaculture activities in Argentina and there, surface water temperature shows an increment that despite leading toward better growth rates, also provokes lack of ovulation, atresia, and a partial or total absence of spawning during the breeding season. During the early life history, low survival rates at hatching and first feeding are also observed. The increase of market size (> 2 kg) has changed management practices, minimising the difference between brood stock and individuals destined for consumption. Thus, the present situation differs deeply from carrying capacities forecasted few years ago and this analysis attempts to contribute to management policies including the idea of adaptation to climate change in the making of decisions.